Relationship Testament QS. Al-Nisa' [4]: 11 and Hadith The Extent of Fara'idh - Noorjaman, Amirudin; Jumhur Salikin, Adang (Journal of International Conference Proceedings, 2023)
The purpose of this research is to find out the relationship between the interpretation of Qs. Al-Nisa with the hadith of the extinction of fara'idh. Method study classified as qualitative by using the approach study References ( Libraries Research . As for method collection data ie use technique document (studies References). The results of this study are QS interpretation relations. Al-Nisa' [4]: 11 and the hadith of the extinction of fara'idh is the widespread attitude of ambiguity practiced by Muslims. This can be seen at least in the attitudes and methods they use in solving religious issues, especially regarding inheritance.